2018
DOI: 10.1016/j.jphotobiol.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The use of suction blisters to measure sunscreen protection against UVR-induced DNA damage

Abstract: The formation of DNA photoproducts caused by solar UVR exposure needs to be investigated in-vivo and in particular in order to assess sunscreens' level of protection against solar genotoxicity. The study's purposes were: i) to evaluate if the roof of suction blisters is an appropriate sampling method for measuring photoproducts, and ii) to measure in-vivo sunscreen protection against cyclobutane pyrimidine dimers. Skin areas on the interior forearms of eight healthy volunteers were exposed in-vivo to 2 MED of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Considering that the fluence of UVA is 20 times larger than that of UVB in sunlight, it may be estimated to be at the origin of a few percent of the overall load of DNA damage. It has been unambiguously shown by different assays that CPD, but not 64PP or Dewar, were efficiently produced by UVA in human cells and skin (37,(50)(51)(52). CPD is now known to be the most frequent photodamage in the UVA range (32,37,53,54).…”
Section: Uv-induced Dna Damage In Melanocytesmentioning
confidence: 99%
“…Considering that the fluence of UVA is 20 times larger than that of UVB in sunlight, it may be estimated to be at the origin of a few percent of the overall load of DNA damage. It has been unambiguously shown by different assays that CPD, but not 64PP or Dewar, were efficiently produced by UVA in human cells and skin (37,(50)(51)(52). CPD is now known to be the most frequent photodamage in the UVA range (32,37,53,54).…”
Section: Uv-induced Dna Damage In Melanocytesmentioning
confidence: 99%
“…The quantification of photoproducts in the DNA extracted from the roof of suction blisters has previously been used to assess the DNA-protection factor of solar products under laboratory conditions ( Josse et al., 2020 , 2018 ). The same technique was used in this study with natural UVR.…”
Section: Resultsmentioning
confidence: 99%
“…The first was the detection of pyrimidine dimers in nuclear DNA. This was performed on the roof of suction blisters, an approach that is less invasive for the skin and the donor than classical biopsies ( Josse et al., 2020 , 2018 ). The second and innovative method was the quantification of the pyrimidine dimers released in urine by the DNA-repair machinery ( Reynaud et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has reported the effect of the same sunscreen at 2 mg/cm 2 after individualised MED-based SSR exposures in skin type I/II volunteers (43). Analyses by HPLC-MS/MS were done on epidermal DNA samples derived from suction blisters.…”
Section: Repeated Exposure Groupmentioning
confidence: 99%